Use of DNA markers for rapid improvement of crops in Africa - Thottappilly, G.; Mignouna, H.; Omitogun, O. (2000)
Genetic engineering and biotechnology are providing new tools for genetic improvement of food crops. Molecular DNA markers are some of these tools which can be used in various fields of plant breeding and germplasm management. For example, molecular markers have used to confirm the identity of hybrids in breeding programmes. Another application of molecular makers is in determining phylogenetic relationships in related species. Information on phylogenetic relationships is useful in facilitating introgression of desireable traits from wild relatives to cultivated crop species. Molecular markers are also been used to construct genetic maps. A genetic map is a collection of genetic markers that have been grouped according to their linkage. Breeders can use DNA maps to carry out marker-assisted selection. This technique enables plants carrying desirable traits such as pest and disease resistance to be selected while still in the seedling stage. Ultimately, this enabls the cloning of the genes to be used for crop improvement. The polymerase chain reaction (PCR) has become a popular technique for molecular genome mapping and the diagnosis of plant pathogens. The technique ensures amplification of specific DNA sequences by the use of primers and the enzyme Tag DNAs (RAPDs), microsatellites and Amplified Fragment Length Polymorphism (AFLP) are some of the most useful molecular markers for DNA fingerprinting. For viral, fungal and bacterial DNA fingerprinting and diagnosis as well as strain differentiation of rhizobia, PCR-RAPD and cDNA probes can be applied alongside with monoclonal antibodies.